UPAYA HUKUM DALAM PENYELESAIAN SENGKETA HASIL PEMILIHAN KEPALA DESA - Fikri, Sultoni (Fakultas Hukum Universitas Muhammadiyah Palu, 2023)
The election of the village head is a form of exercising people's sovereignty and implementing village autonomy. Village head election arrangements are regulated in Undang-Undang Nomor 6 Tahun 2014 Tentang Desa, Peraturan Pemerintah Nomor 43 Tahun 2014 tentang Peraturan Pelaksana UU Desa, dan Permendagri Nomor 65 Tahun 2017 Perubahan Permendagri Nomor 112 tahun 2014 tentang Pemilihan Desa. The implementation of the Pilkades cannot be separated from the development of political dynamics that occurred in the village, which led to conflicts leading to a dispute over the results of the Pilkades. This legal research uses a statutory approach and a conceptual approach. Based on Pasal 37 UU Desa dan Pasal 40 ayat 7 PP Desa, the Regent/Mayor has the authority to settle disputes over the results of the Pilkades. Legal remedies that can be taken for a candidate for village head whose rights have been impaired is to challenge the decision to determine the results of the Pilkades issued by the Regent/Mayor. This decision regarding the determination of the elected village head candidate is the object of filing a lawsuit against the local government.